FRI0298 The Impact of DMARD Co-Therapy on Abatacept Effectiveness in Rheumatoid Arthritis Patients. A Pan-European Analysis of RA Registries. (10th June 2014) - Finckh, A.; Neto, D.; Gomez-Reino, J.; Iannone, F.; Lie, E.; Canhão, H.; Pavelka, K.; Turesson, C.; Mariette, X.; Gottenberg, J.-E.; Hetland, M.
Abstract : Background: Biological disease-modifying anti-rheumatic drugs (bioDMARDs) are generally used in combination with conventional synthetic DMARDs (csDMARDs) in the treatment of rheumatoid arthritis (RA). Anti-TNF agents are more effective in combination with csDMARDs (COMBO) than as monotherapy (MONO), while this is debated with some of the newer bioDMARDs.(1) In particular, no difference was found in patients (pts) with insufficient response to TNF-inhibitors taking abatacept (ABA) in MONO vs. COMBO.(2) Objectives: To compare the effectiveness of ABA started as MONO or in COMBO in RA pts treated in routine care. Methods: This is a pooled observational database analysis of 9 prospective cohorts of RA pts (Czech Republic, Denmark, France, Italy, Norway, Portugal, Spain, Sweden, Switzerland). We included all RA pts treated with ABA with information on concomitant csDMARDs use at initiation of ABA treatment. Primary endpoint was drug retention of ABA, defined as the time between drug initiation and last administration plus one dispensation interval, and analyzed using a Cox proportional hazards model. A secondary endpoint was EULAR good or moderate response rate at one year, estimated by longitudinal interpolation and corrected for drug retention (Lundex (3)). All analyses were adjusted for potential confounders, e.g. calendar year, demographics, country and disease characteristics. Results: We identified 3461 pts initiating ABA with 5475 pt-years of follow-up. Of these, 2314 pts (67%) received ABA in COMBO (53% - methotrexate, 8% - leflunomide, 6% - other csDMARDs) and 1147 pts (33%) in MONO. Pts on MONO were older (mean 59 vs. 57 years, p<0.001) and had longer disease duration (mean 11 vs. 12 years, p=0.005). Other demographic and disease characteristics were balanced. The median retention time of ABA in MONO was 2.02 years (IQR: 1.76 – 2.27) compared to 2.05 years (IQR: 1.90 – 2.22) in COMBO (p=0.76). No significant difference in ABA retention rates was found with or without sDMARD cotherapy (Hazard Ratio (HR) MONO vs COMBO: 1.02 (95%CI: 0.92 – 1.13)). Furthermore, ABA drug retention did not differ between the various sDMARDs cotherapy combinations. Results remained similar when examining only ABA treatment discontinuations for ineffectiveness (HR MONO vs COMBO: 0.97 (95%CI: 0.84 – 1.13)). Furthermore, both the EULAR response rates and the Lundex based on EULAR response rates at one year were similar with or without sDMARD cotherapy (81% EULAR good or moderate responses on ABA MONO vs. 80% on COMBO, p=0.55. Lundex responders 55% on ABA MONO vs. 55% on COMBO, p=0.91). We found no effect modification by country. Conclusions: The results of this large pooled RA population of mostly inadequate responders to anti-TNFs, suggest that ABA retention and response to ABA treatment are not influenced by csDMARDs cotherapy. References: Emery P. et al. Ann Rheum Dis. 2013 Dec;72(12):1897-904. Schiff M et al. Ann Rheum Dis 2009;68:1708–14. Kristensen LE. et al. Arthritis Rheum. 2006 Feb;54(2):600-6. Disclosure of Interest: A. Finckh Grant/research support: Unrestricted Research grant from BMS, D. Neto Grant/research support: Unrestricted Research grant from BMS, J. Gomez-Reino: None declared, F. Iannone: None declared, E. Lie: None declared, H. Canhão: None declared, K. Pavelka: None declared, C. Turesson: None declared, X. Mariette: None declared, J.-E. Gottenberg: None declared, M. Hetland: None declared DOI: 10.1136/annrheumdis-2014-eular.3004